Sociological Dimensions in the Implementation of Salam Contracts in Rambutan Trade Transactions in Tangkiling, Central Kalimantan - Rifai, Agus; Hidayati, Tri; Mohd Zahir, Mohd Zamre (Universitas Islam Negeri Raden Intan Lampung, 2025)
The implementation of salam contracts in agricultural trade often faces tension between classical fiqh norms and local socio-economic dynamics, including in rambutan trade transactions in Tangkiling, Central Kalimantan. The discrepancy between the legal pillars and requirements of salam and trust-based social relations raises questions regarding the validity and normative transformation of such contracts within agrarian communities. This study aims to analyze the sociological dimensions of salam contract implementation in rambutan trade transactions in Tangkiling and to identify the social factors influencing these practices. This research employs a qualitative approach with a field study design, utilizing in-depth interviews, participatory observation, and document analysis. The data were analyzed descriptively and analytically using the perspective of Islamic legal sociology. The findings reveal that salam practices are conducted informally through trust-based transactions, flexible price negotiations, and adaptive arrangements in response to harvest fluctuations. Social solidarity, patron–client relationships, and farmers’ liquidity needs emerge as key determinants shaping transaction patterns. From a normative perspective, several elements of the salam contract are fulfilled; however, flexibility in determining product specifications and delivery time is influenced by local socio-economic contexts. The study highlights the importance of a contextual approach in understanding salam contract implementation and recommends strengthening community-based fiqh muamalah literacy to enhance legal certainty and protection for all parties involved.